A fitting machine learning prediction model for short-term mortality following percutaneous catheterization intervention: a nationwide population-based study - Hsieh, Meng-Hsuen (Ann Transl Med, 2019)
BACKGROUND: A suitable multivariate predictor for predicting mortality following percutaneous coronary intervention (PCI) remains undetermined. We used a nationwide database to construct mortality prediction models to find the appropriate model. METHODS: Data were analyzed from the Taiwan National Health Insurance Research Database (NHIRD) covering the period from 2004 to 2013. The study cohort was composed of 3,421 patients with acute myocardial infarction (AMI) diagnosis undergoing PCI. The dataset of enrolled patients was used to construct multivariate prediction models. Of these, 3,079 and 342 patients were included in the training and test groups, respectively. Each patient had 22 input features and 2 output features that represented mortality. This study implemented an artificial neural network model (ANN), a decision tree (DT), a linear discriminant analysis classifier (LDA), a logistic regression model (LR), a naïve Bayes classifier (NB), and a support vector machine (SVM) to predict post-PCI patient mortality. RESULTS: The DT model was found to be the most suitable in terms of performance and real-world applicability. The DT model achieved an area under receiving operating characteristic of 0.895 (95% confidence interval: 0.865–0.925), F1 of 0.969, precision of 0.971, and recall of 0.974. CONCLUSIONS: The DT model constructed using data from the NHIRD exhibited effective 30-day mortality prediction for patients with AMI following PCI.